Resveratrol-supplemented holding or re-culture media improves viability of fresh or vitrified-warmed in vitro-derived bovine embryos (Research, Society and Development, 2021)
The effect of resveratrol supplementation on fresh (E1) or vitrified/warmed (E2) in vitro produced bovine embryos was investigated by evaluating the time-dependent response. After in vitro production, resveratrol (0.5 µM) was added to the incubation media and after two incubation periods with or without resveratrol, blastocysts were re-cultured for 24h. The rates of re-expansion, hatching, total cell number (TCN), apoptotic cells (ACN), reactive oxygen species (ROS) and intracellular glutathione (GSH) content were evaluated. For E1, the re-expansion rate differed at 6 and 10h within and between treatments (P